(3cJGH GdRcGIs - (3GdgePGfj, QVG Hf eMeO gGOj, J (B1322(3g`s ((3YHO GdLhGO Hf MSf Hf eMeO GdMSjfj GdCROjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3cJGH GdRcGI ; dZI GdWgGQI hGdfeh haj YQa Cgd GdTQY GSe ddMb GdeYQha YfOge GdeYdhe HKHhJg dOjge HfU GdcJGH hGdSfI GdeJhGJQI Hd gj cGdUdGI hGdUjGe ef GdVQhQjGJ jNQL efcQg Yf QHbI GdESdGe (B...s
(3BNQgG (B:s
... (3HYO GTJQGW TjA efgeG aj GSJMbGb GdRcGI gh GdCbhi hEf cGf Gdbhd GdChd Cj GYJHGQ GdYOGdI CMhW hGddg GdYGde HMbGFb CMcGeg GdhUa GdKGdK (B...s
(3ebGHdI Ydi eShOI heHjVI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\720s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis